Desde el dibujo : procesos y prácticas en el campo ampliado del arte : escrituras reflexivas - Melina Airaudo; María Cecilia Irazusta; Micaela Trocello; Liliana Menéndez; Mauricio Cerbellera; Pablo González Padilla; María Florencia Agüero; Paula Roqué Buguñá; Pablo Vinet; Colectivo Bordadoras; Alejandra Escribano; Iris Loza; et al. (2025)
Directora: María Cecilia Irazusta.